Characteristics of Porosity and Permeability of Ultra-High Temperature Perforated Damage Zone in Sandstone Targets - Xu, Changgui; Liang, Hao; Guo, Shusheng (Frontiers in Earth Science, 2022)
Perforating as a widely-applied stimulation technology is becoming incrementally important in unconventional oil/gas development. It can effectively improve deep-lying high-temperature, high-pressure (HTHP), low-porosity, low-permeability reservoirs, eliminate near-wellbore surface pollution, and increase drainage area. Characteristics of damage zone porosity directly reflect perforating performance. To study porosity and permeability of damage zone in sandstone targets, the paper collected sandstone cores from the 3rd section of the Zhuhai Formation to conduct a simulation experiment for HTHP perforation of large-size targets. After the simulation experiment, an automatic scanner was used to find the planar distribution of the porosity and permeability parameters of the 150°C perforation holes in the cores. The study led to two findings. First, the temperature has a minor effect on the hole depth and diameter in a specified scope. The hole depth decreases as the negative pressure increases and the depth decreases as the effective stress increases. Second, a UHP perforated sandstone target is remarkably zone-specific in planar distribution of the hole porosity and permeability. The damage zone can be divided into the fracture zone, the transition zone, the compaction zone and the undisturbed zone. Besides, the zone permeability damage was quantified. These findings can effectively support research on numerical value simulation for HTHP perforation holes. Besides, they can support HTHP well perforating design and improve near-wellbore permeability enhancement and plug removal.